The market of sport supplement in the digital era: A netnographic analysis of perceived risks, side-effects and other safety issues. (2021) - Catalani, Valeria; Negri, Attilio; Townshend, Honor; Simonato, Pierluigi; Prilutskaya, Mariya; Tippett, Anna; Corazza, Ornella
Highlights: The food supplements online context available and was assessed through the use of an automatized web-based monitoring tool (Brand24®) and a further netnographic qualitative analysis of online fitness fora, with regards to the most popular food supplements, the most popular fitness fora, motivations of intake, self-reported side effects and the overall safety perception/reliability of information online. Data retrieved contribute to create a positive narrative on food supplements, linking them to improved health, natural remedies, general and sporting success and superior performances, hence encouraging their intake. In line with a positive web narrative on supplementation, a small percentage of fitness fora users (19%) self-reported associated side effects . Moreover, the most reported side effects do not help depicting the threat that the uninformed use of supplements represents. Indeed, only minor side effects were mostly reported online (e.g. acne, water retention), with very few to none references to much serious ones (e.g. kidney disfunction). These suggests how users are unaware of both the existence and the types of severe risk/side effects that can be associated with food supplements usage. In addition, social media, fora and online resource were found to be increasingly used as the primary reliable sources of information on the efficacy and safety profile of dietary/sportsupplements . Traditional advice on supplement were usually provided by coaches, medical professionals and other more trusted and accountable sources. This study shows how, at date there is a tendency of replacing professional advicewith a range of unsolicited online claims and social media interactions. The lack of control/regulation over the latters, who have a reach of millions of users, makes supplementation a more risky phenomenon. This scenario is further complicated by the emergence of a new cohort of supplement users (general public and amateur sport people) and by a change in the motivations for intake, that are at date mainly related to an improvement of physical appearance, rather than sport performance. The poorly regulated online diffusion of untested fitness supplements could indeed represents a new major challenge, which requires prompt responses to safeguard the health and the safety of supplement users. Although experienced users might be aware of the risks, more vulnerable and inexperienced individuals may be unknowingly exposing themselves to potent and highly toxic drugs. Clinicians should be informed and invited to ask patients about the use of supplements and report suspected adverse events to health agencies. Abstract: Background: The market of sport supplements is expanding worldwide. Such phenomenon is often supported by captivating marketing strategies and social media advertising providing unscientifically founded claims, thus raising safety concerns. The aim of our study is to provide a comprehensive analysis of the online market, patterns of use, perceived risks and other safety issues on supplement use as reported in online fitness communities. Methods: A mixed method approach was employed. An automatized web-based monitoring tool (Brand24®) was used to track the most popular supplements and related discussions according to the number of interactions between users and shares; the number and category of websites; the social media reach; and the most popular hashtags. Results were assessed through a netnographic qualitative analysis of online fitness fora, to identify motivations of intake, self-reported side effects andthe overall safety perception reliability of supplements information online. Results: A social media reach of over four million individuals, inclusive of 18595 posts, emerged from our search. The most cited supplements were "Whey Protein", "Branched Chain Amino-Acid", "Creatine", "Multivitamin supplements" and "Nitric Oxide boosters". Supplements were mainly taken for muscle gain (23%), increase energy (17%), and weight loss (8%). Although the web narrative on supplementation was overall positive, a wide range of side effects were reported by 19% of fitness fora users. These included acne (9%), water retention (9%), stomach pain (9%), rashes (7%), erectile dysfunctions (7%) and weight gain (5%). Concerns about contamination (47%), counterfeit content (17%) and the presence of hidden ingredients (11%) were also recorded. Conclusions: In a poorly regulated context, where unsolicited social media posts have replaced the typical advice provided by professionals, efforts should be made to ensure the reliability of the provided information to avoid the insurgence of unwanted adverse effects and safeguard public health.